EFEKTIVITAS REGULASI PERLINDUNGAN DATA PRIBADI DALAM MENANGGULANGI KEBOCORAN DATA DIGITAL - Dwi Agung Firmansyah (PT. Habe Cendekia Utama, 2025)
The rapid development of digitalization in Indonesia has increased the use of personal data in the public and private sectors, but has been accompanied by a surge in data leaks that threaten privacy, national security, and public trust. Although Law Number 27 of 2022 concerning Personal Data Protection (PDP Law) has been enacted as an effort to strengthen the law, its effectiveness in addressing digital data leaks remains questionable due to weak implementation, limited oversight institutions, and low public digital literacy. This study aims to analyze the effectiveness of personal data protection regulations in preventing and addressing data leaks in Indonesia and to identify factors hindering the implementation of the PDP Law. The research method used is a descriptive qualitative approach with a literature review of secondary sources including scientific journals, official reports, and government regulations. Data analysis was conducted using Soerjono Soekanto's theory of legal effectiveness and the principles of digital data governance. The results indicate that the effectiveness of the PDP Law remains partial due to suboptimal enforcement and dissemination, weak inter-agency coordination, and incomplete implementing regulations. Legal framework reform, increased capacity of oversight institutions, and digital literacy education are needed to realize an adaptive and globally standardized data protection system